Hubungan Faktor Risiko dan Kondisi Penyakit Penyerta dengan Gambaran Foto Toraks pada Pasien Terkonfirmasi COVID-19 - Heni Fatmawati; Zhafirah Rana Labibah; Jauhar Firdaus (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: COVID-19 is a worldwide health problem with a high mortality rate, especially in patients with risk factors. One type of examination to inspect the severity of COVID-19 patients is a chest radiograph. There is a lack of studies on chest radiography features in Indonesia. This study aims to observe the relationship between age, gender, and comorbid conditions with chest radiography features in COVID-19 confirmed.Method: This study was conducted at dr. Soebandi General Hospital uses a cross-sectional design with medical records as the instrument. Chest radiography examination was performed using BSTI classification. Meanwhile, data were analyzed using Chi-Square and contingency coefficient C.Result: The study included 173 patients: 52% were 40-59 years old, 36,4% were 20-39 years old, and 11,6% were ≥ 60 years old; 56,1% were female and 53,9% were male; 50,9% have comorbidities, with hypertension, diabetes, and COPD were the most type of comorbidities. About 48,6% sample had a normal chest radiograph, 27,7% had a mild severity, 17,3% had a moderate severity, and 6,4% had a severe severity. There was a correlation between age and comorbidity with chest radiography features. Otherwise, no correlation was found between sex and chest radiography features.Conclusion: Age and comorbidity were found as significant risk factors for the severity of chest radiograph in COVID-19 with a moderate correlation. However, no correlation was found between sex and chest radiography features.